Notes on Canadian Ablabesmyia Johannsen, with keys to known Nearctic immatures of the genus (Diptera: Chironomidae) - Sæther, Ole A. (Zootaxa, 2011)
x The immatures and males of A. (Karelia) illinoensis (Malloch), A. (K.) philosphagnos Beck et Beck, A. (K.) pulchripennis (Lundbeck), A. (A.) mallochi (Walley), A. (A.) aspera Roback, A. (A.) basalis (Walley) and A. (Asayia) annulata (Say) are redescribed and/or illustrated. A. (A.) basalis (Walley) is regarded as a valid species separate from Nearctic A. (A.) monilis auct nec (L.). Seven species of Ablabesmyia were found from Lake Winnipeg, Manitoba, 3 from Marion Lake, British Columbia while other samples from Alberta to Ontario contained no more than one species. Keys are given to Nearctic immatures of Ablabesmyia. The distribution of Ablabesmyia in Lake Winnipeg is mapped and discussed. The separation of larval instars is shown approximately to follow Dyar’s rule.